PERILAKU PEMILIH BURUH DI KAWASAN INDUSTRI DALAM PEMILIHAN UMUM 2024 KECAMATAN TUALANG KABUPATEN SIAK - Ramadhani, Dwi Zahra; Nisaa, Fadhiilatun (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Workers in industrial areas face various problems, such as unilateral termination of employment (PHK), accelerated retirement, and limited space to voice political aspirations. These conditions are an important background in understanding workers' political behavior, especially in the context of the 2024 General Election. This study aims to describe the voting behavior of workers in industrial areas in the 2024 General Election in Tualang District, Siak Regency. The method used in this study is a descriptive qualitative approach descriptive qualitative approach. Data were collected through in-depth interviews, as well as FGDs with labor unions and documentation of workers in the industrial area of Tualang District, Siak Regency. The main focus of this study is to understand how workers' voting behavior is formed, the extent to which rationality influences their choices, and how working conditions and the position of labor unions contribute to shaping the dynamics of political participation among workers. The results of the study show that the majority of workers vote rationally by considering the vision and mission, work programs, and track records of candidates, as explained in Anthony Downs' Rational Choice theory. However, there is also a tendency to vote based on emotional closeness or local identity, as well as the presence of critical voters who reject money politics. From the perspective of Robert A. Dahl's Polyarchy theory, worker participation is quite inclusive without direct pressure from companies, but political access is still limited due to the lack of polling stations around industrial areas, as well as limited campaign space in the workplace. The conclusion of this study is that labor political behavior in industrial areas is not homogeneous, but rather demonstrates a combination of rationality, pragmatism, and structural limitations. While participation continues, challenges of representation and access remain that need to be addressed to achieve a truly inclusive and participatory democracy. Keywords: Workers, Industrial Areas, Voter Behavior